Justice and Objectivity as Balancing Principles - Rodak, Lidia; Żak, Piotr (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
This paper compares the traditional and modern models of applying law, that is to say, the syllogistic model, based on subsumption and the argumentative model, based on the balancing principle. The common feature of both models is that they indicate certain values that are desired in applying law. The most important value of the first model is the certainty and predictability of the law, while of the second it is fairness, justice and the ability to follow the particular circumstances of each case using the general principles of morality and justice. It seems that the dispute between the traditional and modern models of applying law is, in essence, a dispute regarding the opposite values which are first submitted to the balancing procedure.
Keywords: applying law; syllogistic model; argumentative model